2020
DOI: 10.3390/w12071930
|View full text |Cite
|
Sign up to set email alerts
|

Generalised Linear Models for Prediction of Dissolved Oxygen in a Waste Stabilisation Pond

Abstract: Due to simplicity and low costs, waste stabilisation ponds (WSPs) have become one of the most popular biological wastewater treatment systems that are applied in many places around the globe. Increasingly, pond modelling has become an interesting tool to improve and optimise their performance. Unlike process-driven models, generalised linear models (GLMs) can deliver considerable practical values in specific case studies with limited resources of time, data and mechanistic understanding, especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Mathematical modeling (MM) can forecast and improve the WSPs performance for various climatic regions [2,6,25]. Turkey's wastewater treatment systems are only numerically modeled [27][28][29]. Nevertheless, global optimization algorithms, such as the generalized reduced gradient (GRG) and the interior point, have never been employed to model WSPs in various climatic regions of any country [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical modeling (MM) can forecast and improve the WSPs performance for various climatic regions [2,6,25]. Turkey's wastewater treatment systems are only numerically modeled [27][28][29]. Nevertheless, global optimization algorithms, such as the generalized reduced gradient (GRG) and the interior point, have never been employed to model WSPs in various climatic regions of any country [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Turkey's wastewater treatment systems are only numerically modeled [27][28][29]. Nevertheless, global optimization algorithms, such as the generalized reduced gradient (GRG) and the interior point, have never been employed to model WSPs in various climatic regions of any country [28,29]. This study fills this gap by optimizing the WSPs for all climatic regions of Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, statistical models can be used to predict DO with less amount of data and resources. Pham et al (2020) developed several generalized linear models to predict DO. They showed that statistical models can predict DO with reasonable errors.…”
Section: Introductionmentioning
confidence: 99%
“…This special issue consists of fourteen selected articles, that cover a wide spectrum of Ecosystem Services (ES) of lakes and reservoirs, including: (1) water purification [1,2];…”
mentioning
confidence: 99%
“…Optimizing the operation of WSPs, Pham [1] applied a data-driven model to investigate the key driving factors of dissolved oxygen (DO) in FPs and MPs. The results showed that the concentration of algae had a strong impact on DO level near the water surface, while organic matter was the most influential factor on DO variability at the bottom of the pond.…”
mentioning
confidence: 99%